Detection of carvacrol in essential oils by electrochemical polymerization - Bertuola, Marcos (2020)
Carvacrol (Carv) and thymol (TOH), components of essential oils, are known by their antimicrobial and antioxidant activity. However, Carv but not TOH seems to be the responsible of anti-inflammatory and inhibition of Cu corrosion properties. Since Carv and TOH are positional isomers, their identification is tricky and GC-MS is usually required. To find simple and inexpensive methods that allow the detection of Carv in presence of TOH (e.g. essential oils), cyclic voltammetry and chronoamperometry tests using Pt and Cu as electrodes in TOH and Carv containing mixtures and essential oils were made. Electrochemical and ATR-FTIR results show that pure phytocompounds and mixtures lead to the formation of polymeric layers on both metallic surfaces. Results show that only Cu is suitable for Carv detection. Potentiostatic and potentiodynamic detection is simple and conclusive in Carv þ TOH mixtures and in essential oils due to the formation of a homogeneous blocking Carv electropolymeric layer on Cu.